(untitled) (American Journal of Islam and Society, 2014)
I should begin by confessing that I have been a fan of Michael Muhammad Knight’s work ever since I first read his novel, The Taqwacores, and his travel memoir, Blue-Eyed Devi: A Road Odyssey through Islamic America, back in 2007. I have since read all of his books and have taught several of them in my courses on contemporary Islam and Islam in North America. I regularly teach his account of the hajj from Journey to the End of Islam in my first-year “Introduction to Religion” course. I consider his book on the Five-Percent Nation, The Five Percenters: Islam, Hip Hop, and the Gods of New York, to be one of the finest ethnographies of a religious community ever penned. I was therefore pleased to find I have a blurb on the back of Tripping with Allah in which I praise him for his talent, his authenticity, and his passion. I consider the author a great writer. I envy his skill with language, his creative intellect, and, most of all, his formidable work ethic. After all, this is his ninth book since the publication of The Taqwacores (Soft Skull Press: 2004). However, I sometimes wonder exactly for whom he is writing because his books assume a sophisticated audience with backgrounds in a wide range of topics from the history of Islam to American popular culture. In the final pages of Tripping with Allah, Knight sums up his career so far with this remarkable paragraph. I’ve spent roughly twenty years as a Muslim of some form or other, a crazy convert and then an ex-Muslim, progressive Muslim, ghulat Shi’a, Nimatullahi dervish, Azrael Wisdom, Mikail El, Islamic Gonzo, “godfather of Muslim punk rock,” Seal of Muslim Pseudo and now Pharmakon Allah, Muhammadus Prine, Quetzalcoatl Farrakhan who trips and says Fatima Kubra but has this goofy idea of taking up the way of the salaf, and Dr. Bruce Lawrence just called me a malamatiyyah at a lecture in Vancouver. (p. 248) This paragraph is striking because it assumes so much of its reader, including a rather encyclopedic knowledge of Islam, African-American religious traditions, pop-culture, and what Frank Zappa might have called the “conceptual continuity” of the author’s entire body of work. The line that grabbed me most powerfully was the image of Bruce Lawrence, the eminent scholar of Islam and Sufism, referring to Michael Knight as a malāmatīyah. This term, ...